Ontology-based nutrient solution control system for hydroponics - Phutthisathian, Areeworn; Pantasen, Nakulrad; Maneerat, Noppadol (My University, 2011)
This paper presents the Ontology-based Nutrient Solution Control System for Hydroponics with Protégé. We consider variables of electrical conductivity (EC), Potential of Hydrogen ion (pH), intensity of solution, species of plants and the relation of the device in the system for supporting to make the suitable decisions with the control system of hydroponic nutrient solution. © 2011 IEEE.
Keywords: Hydroponics; Nutrient Solution; Ontology